Analysis of Child Labour among Rural Household of Oyo State, Nigeria - Idowu, Alao Bashir; Amos, Olasore Abiodun; Olabisi , Aremu Adeola (Asian Journal of Agriculture and Rural Development, 2013)
This study is on analysis of child labour determinants among the farming households of Oyo State, Nigeria. Data for the study were obtained from 120 respondents from the target group using a three-stage sampling procedure and analyzed using descriptive statistics and logistic model. Results showed that 85% of the respondents are male. The mean age of the respondent is 58 years 74.16% of them are married. Religions of the respondent are 40%, 53.33%, and 6.67% for Christianity, Islam and traditional religions respectively. 43.33% of the households have no formal education. The average household size is 11. The average farm size of the respondent is 9.12ha. The mean income per household is less than N150 ($1) per day. Age of the household head and the farm size were significant at 5%. Age of household head, household size and number of male child in the house respectively have positive coefficients. Gender of household head, educational level, number of female child and household income has negative coefficients. This implies that as these variables increase child labour will reduce.